2018
DOI: 10.1002/ps.5205
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of CarE genes from the Chinese white pine beetle Dendroctonus armandi (Curculionidae: Scolytinae) and their response to host chemical defense

Abstract: Transcription levels of CarE genes suggest some relationship with the detoxification of terpenoids released by host trees. The functions of bark beetle esterase are mainly in hydrolyzing the host chemical defense and degrading odorant molecules during host selection and colonization. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
(143 reference statements)
0
11
0
Order By: Relevance
“…GST gene transcription was more sensitive in females to monoterpenes than that in males, but 3-carene was a special stimulus to males which caused extensive overexpression of GSTs. (+)-3-carene lead to higher male beetle mortality in fumigant toxicity tests than other terpenoids (Dai et al, 2015), and also had a greater impact on the transcription of most esterase genes (Dai et al, 2019). The higher expression levels of GSTs in females had a relationship with the resistance to host chemicals which might be also involved in female oviposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GST gene transcription was more sensitive in females to monoterpenes than that in males, but 3-carene was a special stimulus to males which caused extensive overexpression of GSTs. (+)-3-carene lead to higher male beetle mortality in fumigant toxicity tests than other terpenoids (Dai et al, 2015), and also had a greater impact on the transcription of most esterase genes (Dai et al, 2019). The higher expression levels of GSTs in females had a relationship with the resistance to host chemicals which might be also involved in female oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional expression levels of D. armandi GSTs were normalized to the transcript levels of β-actin (KJ507199) and CYP4G55 (KR012821), as these two genes have stable expression levels in different stages, tissues, and feeding or terpenoids treatment (Dai et al, 2019). By calculating the geometric mean of these two genes, the accuracy of the relative expression level results can be improved.…”
Section: Real-time Qpcrmentioning
confidence: 99%
“…The specific expression patterns of EST genes in different developmental stages or sexes suggesting their possible functional roles (Campbell et al, 2003;Yang, 2016;. Some secreted ESTs (JHE and β-esterase) regulate development or reproduction via regulating the hormone and pheromones signal in insects (Dai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bark beetles have faced the toxic compounds of their host plants through different enzymes and molecular mechanisms (Robert et al, 2013; Dai et al, 2016, 2018; Chiu et al, 2019) of their own or from different symbiont microbes such as yeast, fungi, and bacteria. Some studies have shown that bark beetles-associated bacterial and filamentous fungi have developed different strategies and molecular mechanisms to excrete, metabolize into non-toxic compounds or sequester diverse terpenoid compounds (DiGuistini et al, 2011; Adams et al, 2013; Haridas et al, 2013; Lah et al, 2013).…”
Section: Discussionmentioning
confidence: 99%